Proceedings of the 2004 National Seminar on Banking and Allied Matters for Judges - National Seminar on Banking and Allied Matters for Judges; Chartered Institute of Bankers of Nigeria; National Judicial Institute (Nigeria) (Lagos : Chartered Institute of Bankers of Nigeria, 2004)
The proceedings of the National Seminars on Banking and Allied Matters for Judges organised annually by the Chartered Institute of Bankers of Nigeria and the National Judicial Institute (Nigeria). Papers presented usually deal with contemporary banking and allied issues in the judicial contexts.
Includes bibliographical references.
oif 14/07/14
Ref
Keywords: Banking law -- Nigeria -- Congresses; Judges -- Nigeria -- Congresses